Anemia Pada Pasien dengan Gagal Ginjal Kronik yang Menjalani Hemodialisa - Zaenal Arifin; Ilham; Baiq Ruli Fatmawati (LPPM STIKES Mataram, 2023)
Introduction: Chronic kidney disease is characterized by the body's inability to maintain homeostasis, accompanied by uremia and insufficiency of renal function. Chronic kidney disease or chronic kidney failure can cause several complications, one of them is anemia. Purpuse: The aim of this study was to identify anemia that occurs in patients with chronic renal failure undergoing hemodialysis. The design of this research is descriptive with a cross-sectional approach. Methods: This research will be carried out in a hospital hemodialysis room. West Nusa Tenggara Province Regional General. The population in this study were patients with chronic renal failure (CKD) undergoing hemodialysis. The samples in this study were CKD patients who were undergoing hemodialysis in September 2023 using a consecutive sampling technique. The instruments used in this research used questionnaires and observation sheets. Data collection was based on secondary data listed in the patient's medical records. Result: The results of the study showed that the average hemoglobin level of patients with chronic renal failure undergoing hemodialysis was 9.15. Meanwhile, based on the anemia category, it is known that the majority of patients with chronic kidney failure who underwent hemodialysis were in the mild anemia category, namely 18 people (40.9%). Suggestions: for future researchers are that they can carry out further research related to anemia in patients with kidney failure.